If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + -3 = 2b + -7 Reorder the terms: -3 + b = 2b + -7 Reorder the terms: -3 + b = -7 + 2b Solving -3 + b = -7 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. -3 + b + -2b = -7 + 2b + -2b Combine like terms: b + -2b = -1b -3 + -1b = -7 + 2b + -2b Combine like terms: 2b + -2b = 0 -3 + -1b = -7 + 0 -3 + -1b = -7 Add '3' to each side of the equation. -3 + 3 + -1b = -7 + 3 Combine like terms: -3 + 3 = 0 0 + -1b = -7 + 3 -1b = -7 + 3 Combine like terms: -7 + 3 = -4 -1b = -4 Divide each side by '-1'. b = 4 Simplifying b = 4
| 1.5(3y-1)+2=5y | | -5-7(1+8z)=-30 | | 6+2n=4n+2 | | -10t=-18-19t | | 4t+48n=100 | | 5(0-4)-9=3-2(0+16) | | 2a+6=a+2 | | 5X-13=15+17x | | 3=7x^2+5 | | (25b-7)-6(4b+4)=-6 | | (5b-1)(3b+2)= | | 14/2=x | | -5-7(1+8z)=30 | | -3d-4+9d=16 | | 4x^12-5x^6-14=0 | | 3n+3-4= | | -2(-9m-2)-1=27+10 | | 4x-18=8(x+6) | | -12+3b=-6+2b | | -3/x=6 | | (8a+3b-9)+(-17a-2b+8)= | | 2(4x-3)-8=1+2x | | 7a-1=5a+13 | | 2=.2x-.4x-7 | | 2=.02x-0.4x-7 | | -27+3n=2(7n+4) | | 2n+4=-3n+14 | | -7(p+8)=2 | | 8x+2(x+6)=2x+15 | | (7b-6)-3(2b+4)=-3 | | 1/3x^2-1/18x-11/9=0 | | -2(k+16)=-44 |